Controle e publicidade eficazes de créditos de carbono para incremento do investimento empresarial no enfrentamento da crise climática - Ferraz, Patricia André de Camargo (2023)
The United Nations Framework Convention on Climate Change, in a multifaceted strategy of fighting global warming effects and aiming at providing funding means for projects to reduce greenhouse gas emissions and capture, adopted, among other market mechanisms, the Sustainable Development Mechanism (SDM), which comprises the issuance and trading of carbon credits, including those related to forests. In order to develop the carbon credit market, it must have legal certainty, transparency, control, and, thus, integrity. The Brazilian Real Estate Registry Office, fully operating and structured in a way to provide legal certainty, transparency, and control to real estate businesses, under efficient private management and inspected by the Judiciary Branch, and with no development and implementation costs for the Government, is a highly capillary, resilient mechanism promptly available to provide such attributes to the regulated and voluntary Brazilian carbon credit markets and to contribute to the efforts for fighting global warming.